2019
DOI: 10.4081/idr.2019.8208
|View full text |Cite
|
Sign up to set email alerts
|

Present and Future of Siderophore-Based Therapeutic and Diagnostic Approaches in Infectious Diseases

Abstract: Iron is an essential micronutrient required for the growth of almost all aerobic organisms; the iron uptake pathway in bacteria therefore represents a possible target for novel antimicrobials, including hybrids between antimicrobials and siderophores. Siderophores are low molecular weight iron chelators that bind to iron and are actively transported inside the cell through specific binding protein complexes. These binding protein complexes are present both in Gram negative bacteria, in their outer and inner me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 62 publications
1
29
0
2
Order By: Relevance
“…Hydroxamic acids have found many applications in medical and agricultural practices [109] and as probes [1,3]. Their medical use can be therapeutic or diagnostic [110].…”
Section: Applications Of Hydroxamate Molecules and Hydroxamate Siderophoresmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydroxamic acids have found many applications in medical and agricultural practices [109] and as probes [1,3]. Their medical use can be therapeutic or diagnostic [110].…”
Section: Applications Of Hydroxamate Molecules and Hydroxamate Siderophoresmentioning
confidence: 99%
“…All bacteria susceptible to the microbicidal activity of these hydroxamate sideromycins were found to have the FhuA receptor in their membranes. These sideromycins function better under iron starvation conditions than under conditions of sufficiency [3]. Iron starvation can be achieved by using biostatic agents (strong chelators that bind iron tightly).…”
Section: Natural Conjugates (Sideromycins)mentioning
confidence: 99%
See 1 more Smart Citation
“…Before the efficient market hypothesis was put forward, there were many literatures on the predictability of securities prices. For example, Liang et al [13] found that the changes of securities prices and commodity prices in European and American markets were random; Nápoles et al [14] found that the stock price time series in the United States is random and cannot be distinguished from the series generated by a random number series; Tonziello et al [15] found that the characteristics of stock price behavior are similar to those of particles in fluid and accord with the characteristics of random walk. It is these empirical studies that found the unpredictability of market price that prompted economists to think about the reasons for the random walk of securities price and finally promoted the formation of efficient market hypothesis theory.…”
Section: Related Workmentioning
confidence: 99%
“…These results also impact organic chemists studying antibiotic natural products, especially those targeting bacterial virulence. Siderophore-mediated iron-acquisition as an antibiotic target has been a topic of broad interest 20 and has recently even resulted in an FDA approved drug (cefiderocol, brand name Fetrojaâ). 21 The SAR from the isolation report points to an asof-yet unidentified relationship between the activity of the cahuitamycins and their similarity to the siderophores of A. baumannii.…”
Section: H Nmr Of Our Syntheticmentioning
confidence: 99%